Smartamine M Supplementation Reduces Inflammation but Does Not Affect Performance in Receiving Beef Heifers - M. S. Grant; H. F. Speer; W. R. Hollenbeck; R. N. Wahl; N. D. Luchini; D. A. Blasi; E. C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:This study was conducted to evaluate the ability of supplemental methionine to improve health, inflammation status, and performance of receiving cattle. Study Description:A group of 384 crossbred heifers (initial weight 489 lb) of Tennessee origin were used in a 45-day receiving trial with limit-feeding to evaluate the effects of supplemental methionine (Smartamine M; Adisseo, Alpharetta, GA) on health, inflammation, and performance. Cattle received either 0 (control) or 10 grams/day Smartamine M, a ruminally protected methionine product. Plasma haptoglobin levels measured on days 0, 14, and 45 were used as a biomarker of inflammation. The BottomLine:Supplemental methionine supplied by Smartamine M does not improve performance but reduces inflammation and possibly improves immune function in receiving heifers.
Keywords: methionine; receiving cattle; haptoglobin